The impact of coronary chronic total occlusion angioplasties on left ventricular function. (2nd May 2022) - Costa, H; Santo, ME; Fernandes, R; Mota, T; Palmeiro, H; Bispo, J; Guedes, J; Carvalho, D; Mimoso, J; Vinhas, H; Jesus, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Coronary chronic total occlusions (CTO) are relatively common findings in the context of coronary angiography. The indication for revascularization of this type of lesions remains controversial. The recommendations of international cardiology societies consider the treatment of CTO by percutaneous coronary intervention (PCI) in selected patients, but this technique is not yet widely used in this context. Objectives: Analyze the impact of CTO PCI on left ventricular function (LVEF), measured by the recovery of LVEF (positive variation-PV). Also analyze the profile of patients with greater cardiac functional benefit. Methods: Observational and retrospective study with descriptive and comparative analysis of patients undergoing CTO PCI, between 1 January 2019 and 31 December 2020. Descriptive analysis was carried out regarding the demographic and clinical characteristics. Chi-Square test was used for categorical variables and the T-Student test for numerical variables, with a significance level of 95%. CHIAD algorithm was applied to identify patient profiles, whose dependent variable was LVEF variation, and fixed 15 parent nodes and 5 children nodes. For statistical analysis, SPSS 24.0 was used. Results: N177 patients were identified, with a mean age of 65.4 years (standard deviation of 11.1), 51% were female. The most frequent location of CTO was the right coronary (RCA) in 41.2%. The mean LVEF was 46.9% with standard deviation 9.9. 61.5% of patients had PV, on average rising 14% (p=0, 000). The patients who benefited the most were those with LVEF <49% (81.8% of PV - p = 0.000), compared to those with LVEF [49%-58%] (41.7% of PV - p=0.000) and LVEF> 58% (30.8 % of PV - p=0.00). In the multivariate analysis in a logic of dependency and profiles, patients with LVEF <49% (81.8% PV - p=0.000), who didn´t develop HF symptoms at 180D (85.7% PV - p=0.001) and angor at 30D (90.5% PV - p = 0.020) were those with the highest PV of LVEF. Conclusion: This analysis highlights the experience of the angiography laboratory. In this pool, the RCA was the most affected by CTO. Most patients had LVEF recovery, rising by an average of 14%. Lower LVEF patients appear to have greater potential for left ventricular recovery. The analysis suggests that benefit were greater in patients with medium range or reduced LVEF that didn´t develop post-procedure HF symptoms and angina.